The Role of Childhood Abuse and Social Health on Bullying among Prisoners - Mahnaz Farahmand; Hanieh Tayebi (جامعه شناسی کاربردی, 2025)
Bullying is a relatively common phenomenon among prisoners with both short-term and long-term negative consequences for the bully and the victim. It often manifests as a strategy to gain power and control over others. A significant factor influencing the development of aggressive and bullying behaviors is childhood abuse, which encompasses physical, emotional, and sexual abuse, neglect, and exposure to domestic violence. These experiences can adversely affect an individual's social health. Social health refers to a person's ability to establish positive and constructive relationships and feel a sense of belonging within society. Enhancing social health can help mitigate bullying behaviors. Research indicates that prisoners with adverse childhood experiences frequently struggle with communication and social belonging, leading them to engage in antisocial behaviors and bullying (Lemon, 2020). In this context, the present study sought to address the following key questions: What is the prevalence of bullying behavior among prisoners who commit violent offenses? What role do childhood abuse and prisoners' overall health play in the development of bullying behaviors? Answering these questions can provide deeper insights into the causes of violent behaviors and bullying in prisons, ultimately paving the way for practical solutions to reduce these issues.